Serum Resistin levels in bladder cancer - Mohammadi, Mahmoud; Hosseini, Jalil; Fallah Karkan, Morteza; Hedayati, Mehdi (Archives of Men’s Health, 2018)
Background: Adipokines play a role in pathogenesis and progression of certain cancers. Resistin is an adipokine with diverse findings in disease development and progression. The present study aimed to determine Resistin serum levels in bladder cancer cases in order to identify novel tumor markers. Methods: This research was based on a case-control study, including 45 patients with bladder cancer and 45 healthy controls. Resistin levels were measured by ELISA in both groups. Height and weight were measured and body mass index (kg/m2) was calculated. Results: Resistin levels were significantly different between bladder cancer and the control group (p<0.0001) but Resistin levels in different stages were not significantly different. Also there was no correlation among sex, age, body mass index and the serum Resistin levels. Conclusions: These results suggest that changes in serum Resistin levels play an important role in the diagnosis and could act as a biomarkers for bladder cancer.